Influence of Ecological Requirements on the Choice of Equipment for Treatment of Hot Gases Emissions ... - Štrumberger, Nada; Koljatić, Vjekoslav; Maletić, Natalija (Promet - Traffic&Transportation, 2012)
Control of air pollution caused by ship’s power plant and itsreduction to the desired limits can be achieved in various ways.One of the most significant and acceptable at this stage of today’stechnological development is the catalytic converter operatingon the principle of the selective catalytic reduction (SCR).Considering air pollution from ships, circumstances are rathercomplex. Namely, the International Convention for the Preventionof Pollution from Ships (MARPOL 73/78) in addition tothe general and common rules concerning every kind of pollutants,anticipated specific provisions in the Annexes. For instance,Annex VI refers to the prevention of air pollution bysmoke and gas emissions from ships and its adoption is expectednot earlier than 2003, as it has to be signed by at least 15countries, that is by at least the number of countries that own50% of the world’s gross tonnage. At present, only local andpmtiallaws are in force, which are valid in the whole tradingarea (zone of economic interest) up to 200 Nm off the coast,with a requirement for ships built after 1995 to be filled at leastwith a Selective Catalytic Reduction System (SCR).